Fiscal Policy Instruments in Islam: Ghanimah and Fa'i - Heris Suhendar; Yadi Janwari; Sofian Al-Hakim (al-Afkar, Journal For Islamic Studies, 2024)
Ghanimah and fa'i are one of the fiscal policy instruments implemented by the Prophet Muhammad SAW which was later followed by the government of Khulafaur Rasyidin. The research aims to examine the function of allocation, distribution and stabilization of ghanimah and fa'i fiscal policies by the Prophet Muhammad SAW to his companions from various ulama opinions. This type of research is literature review research with a historical and conceptual approach. Research materials were obtained from library materials using documentation techniques. The research results found that: 1) state revenues are allocated from ghanimah and fa'i fiscal policy instruments based on text instructions; 2) there are differences of opinion among ulama in the distribution of ghanimah and fa'i; and 3) the social and economic conditions behind the various development policy directions during the time of the Prophet SAW and his companions, resulting in different fiscal policy stabilization functions.